Master weavers of the Andes - Pilafian, Peter (Cineco [production company], 1977)
Examines the craft of weaving as practiced by the Quechua Indians near Cuzco, Peru. Points out that except for the use of chemical dyes, the processes of spinning and weaving are practical as they have been for centuries.